PENGAPLIKASIAN MEDIA GAME ONLINE “BERLAYAR MENCARI HARTA KARUN” KEPADA KENAIKAN PENGETAHUAN SAYUR DAN BUAH PADA ANAK MUDA USIA 15-21 TAHUN - Danisa Alifa Salsabila; Ratih Kurniasari (Universitas Airlangga, 2022)
Background: Consumption of vegetables and fruit for young people in Indonesia is still far from the sufficient category (<400g/day). One of the contributing factors is the low knowledge of balanced nutrition, especially in the guidelines that recommend consuming vegetables and fruit per day. Online game media is used as an effort to increase young people's knowledge of vegetables and fruits because they prefer technology-based games. Objectives: Measuring the influence of the application of the online game